THE USAGE OF DECISION SUPPORT SYSTEMS FOR IMPROVING MANAGERIAL DECISION MAKING PROCESS - Stojkovski, Viktorija (Horizons - International Scientific Journal, 2020)
The ten main managerial roles are classified into three categories and one of them is decision making. Managers need timely information to perform their roles in this category. However, managerial decision-making is synonymous with the whole managerial process. The environment in which managers operate today is much more complex, and the trends themselves lead to increasing complexity. Due to a number of factors, such as new technologies, global markets, competition and political stability, managers are increasingly faced with the choice of multiple alternatives, with higher costs due to mistakes made and greater uncertainty about the future. As a result of these changes in the environment, managers need to learn how to use the new tools and techniques developed to support their decision making. Individual, group, and organizational success is particularly important, so information systems research is moving toward finding ways to improve support for the decision-making process. Therefore, different information systems are designed, developed and implemented to provide the needed support. This paper focuses on a specific research done on the territory of the Republic of North Macedonia to determine the impact that systems have in their company. The survey involved 52 managers from different levels of decision making, from medium to large companies in the Republic of North Macedonia, and the purpose of this research is from obtained results to identify the impact of the decision support systems (DSS) on the degree of managerial satisfaction and the impact of these systems on company productivity.